Association of Marijuana Use with Changes in Cognitive Processing Speed and Flexibility for 17 Years in HIV-Seropositive and HIV-Seronegative Men. (21st March 2019) - Okafor, Chukwuemeka N.; Plankey, Michael W.; Li, Michael; Chen, Xinguang; Surkan, Pamela J.; Shoptaw, Steve; Martin, Eileen; Cohen, Ronald; Sacktor, Ned; Cook, Robert L.
Abstract: Background : The long-term effects of marijuana on cognition, particularly in the context of HIV is not clear, as extant research shows mixed findings. Objective : To determine associations between current and cumulative exposure to marijuana and changes in cognitive processing speed and flexibility in 788 HIV-seropositive (HIV+) and 1, 132 HIV-seronegative (HIV−) men followed for up to 17 years in the Multicenter AIDS Cohort Study. Results : Among HIV+ men only, current daily marijuana use compared to none-use, was significantly associated with a greater annual percentage decline in cognitive processing speed assessed with the Trail Making Test A (TMTA) (β=−0.41, 95% confidence interval (CI): −0.88, −0.03, p =0.03)] and Symbol Digit Modalities Test (SDMT) (β= −0.14, 95% CI: −0.28, −0.01, p =0.04). Further, monthly marijuana use was associated with greater annual percentage decline in cognitive flexibility assessed with the Trail Making Test B (TMTB) (β= −0.70, 95% CI: −1.34, −0.05; p =0.03] and cognitive processing speed (SDMT) (β= −0.21, 95% CI: −0.40, −0.01, p =0.03). Among the HIV− men only, each 5-marijuana use-years (equivalent to 5-years of daily marijuana use) was significantly associated with a 0.17 annual percentage decline in cognitive processing speed only (TMTA) (β= −0.18, 95% CI: −0.36, −0.01; p =0.04). Conclusions : Our findings suggest that marijuana use, particularly current use, may be associated with worse cognitive processing speed, but the magnitude of the estimates was not clinically meaningful.